Debt management for development protection of the poor and the millennium development goals - Raffer, Kunibert; Edward Elgar Publishing (Northampton, Mass. : Edward Elgar, 2010)
This book exposes intolerable global double standards in the treatment of debtors and argues that fairness, economic efficiency and principles common to all civilized legal systems, must and can be applied to so-called "developing countries", or Southern sovereign debtors.
1. Brief history of debt management until 1989 -- 2. Brief history of debt management after 1989 -- 3. In quest of solutions : sovereign insolvency proposals, collective action clauses and recent country cases -- 4. Gleneagles, the Multilateral Debt Relief Initiative and the US crisis -- 5. The Raffer Proposal : an international chapter 9 for countries -- 6. Debtor rights and fairness to creditors in rule of law-based insolvency systems -- 7. MDGs, debt distress and poverty : theoretical roots of policies protecting the poor in debtor countries -- 8. Poverty, debtor protection and the MDGs -- 9. Debt distress, global public goods and a global development partnership -- 10. NGO advocacy for debt reduction cum debtor protection -- 11. The concept of sustainability of international financial institutions -- 12. Problems of overoptimism and ownership -- 13. MDGs and preferred creditor status -- 14. Lending or granting : ODA and the MDGs.
Includes bibliographical references (p. 278-295) and index.
Keywords: Debts, External -- Developing countries; Debt relief; Electronic books